2016
DOI: 10.1111/cup.12787
|View full text |Cite
|
Sign up to set email alerts
|

The role of DOG1 immunohistochemistry in dermatopathology

Abstract: DOG1 is a novel marker for identifying intercellular canaliculi and is a potential immunomarker of myoepithelial cells specific to mammary glands, anogenital mammary-like glands and tumors originating therein.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
2
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 30 publications
(53 reference statements)
1
2
0
Order By: Relevance
“…Cutaneous mixed tumors have been thought to show multilineage differentiation along the lines of the folliculo-sebaceous-apocrine unit. 24 However, a previous report argued the possibility of eccrine differentiation in cutaneous mixed tumors, 29 which was supported by the results of our study. Cutaneous mixed tumors have also been reported…”
Section: Discussionsupporting
confidence: 91%
“…Cutaneous mixed tumors have been thought to show multilineage differentiation along the lines of the folliculo-sebaceous-apocrine unit. 24 However, a previous report argued the possibility of eccrine differentiation in cutaneous mixed tumors, 29 which was supported by the results of our study. Cutaneous mixed tumors have also been reported…”
Section: Discussionsupporting
confidence: 91%
“…The main channels mediating Cl − secretion at the luminal membrane of sweat gland acinar cells are CaCCs [53, 66, 67]. Recent studies have shed light on the molecular nature of the CaCCs in murine and human sweat glands [53, 61, 66, 68, 69]. Bestrophin 2 (BEST2) is a CaCC that is necessary for sweat secretion as Best2 −/− mice showed a complete defect in spontaneous sweat production [61].…”
Section: Mechanism Of Salt and Fluid Secretion In Eccrine Sweat Glmentioning
confidence: 99%
“…Fifty-nine out of 60 invasive carcinoma cases showed negativity and one case shows weak positive for p63 expression with a specificity of 1.66% which is higher than our study [ 5 ]. Goto has studied the role of DOG1 immunohistochemistry in dermatopathology which also showed that among 21 cases of fibroadenoma breast, nine cases were positive for DOG1 expression with specificity of 43% [ 13 ]. In a study conducted by Swalchick et al, nine out of 11 cases of fibroadenoma show DOG1 positivity with a specificity of 82% [ 14 ].…”
Section: Discussionmentioning
confidence: 99%